‘Working from home is better than going out to the factories’ (?): Spatial Embeddedness, Agency and Labour-Market Decisions of Women in the City of Delhi - Sonal Sharma; Eesha Kunduri (South Asia Multidisciplinary Academic Journal)
This paper explores the spatiality and temporality of women’s decisions to navigate particular forms of paid work, through means of a comparative analysis of three different sites and forms of work—at one’s own home (as home based workers), someone else’s home (in the form of paid domestic work) and conventional workplaces like factories (as shop-floor workers and as cleaners). By contextually situating the varying expressions of choice across the three sites, the paper argues that women’s efforts to choose one kind of work arrangement over another are embedded in the power and control that certain spaces of work entail. It further posits that women workers actively seek to reshape and redefine these spaces, through conscious negotiations in everyday practice as well as discourse.